Effects Of Saffron (Crocus Sativus Linn) Supplementation On Happiness And Quality Of Life In Healthy Adults: A Randomized Double Blind Clinical Trial (Journal of Pharmaceutical Negative Results, 2023)
Background: Saffron is a well-known spice and herbal medicine whose health benefits and therapeutic effects have been widely studied. Also, its properties in exhilarating and boosting brain power have been emphasized in Persian medicine. Since few studies have been performed on the saffron effects in healthy people, this study intends to evaluate its effects on promoting happiness and quality of life in healthy adults.Material and Methods: Fifty-two healthy adults were randomly allocated to two groups in an equal ratio. 75 mg saffron powder was prescribed for intervention groups twice a day for two weeks, and the other group received a placebo. The Oxford happiness questionnaire (OHQ) and 36-item Short Form Survey (SF-36) scores were evaluated as outcome measures. Also, their body temperature, blood pressure, heart rate and respiratory rate were compared.Results: Fifty patients completed the study. The two groups were similar in demographic characteristics and mental health assessed by 28-item General Health Questionnaire (GHQ-28). After the intervention, no significant difference was observed between the two groups in terms of the SF-36 questionnaire variables. Although the happiness questionnaire scores in both groups improved significantly, the difference between the saffron and placebo groups was insignificant. Moreover, changes in blood pressure, body temperature, heart rate, and respiratory rate were not significantly different within and between groups.Conclusion: The study showed that daily consumption of 0.15 g of saffron for two weeks in healthy individuals did not change their quality of life and happiness scores compared to the placebo group. This dose of saffron was well tolerated without any serious adverse effects.